2019
DOI: 10.3390/catal9121020
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of Catalytic Processes through the Pellet Structuring: Steady-State Properties of a Bifunctional Catalyst Pellet Applied to Generic Chemical Reactions and the Direct Synthesis of DME

Abstract: Structuring of different types of catalytic active centers at a single-pellet level appears to be a promising and powerful tool for integration and intensification of multistep solid-catalyzed chemical reactions. However, the enhancement in the product yield and selectivity strongly depends on the proper choice of the distribution of different catalysts within the pellet. To demonstrate potential benefits from properly designed catalyst pellet, numerical studies were conducted with the aid of the mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Moreover, it is reported that in hybrid pellets, deactivation may also occur because of the close interaction between the two active phases, possibly leading to detrimental cross migration of elements at the boundaries . The core@shell catalysts are proposed as alternative to the mechanical mixture and the hybrid configurations, as the diffusion lengths are significantly reduced ,, while allowing for a better temperature control . Besides, the core@shell design significantly reduces the contact area between the active phases, partially preventing the aforementioned deactivation .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it is reported that in hybrid pellets, deactivation may also occur because of the close interaction between the two active phases, possibly leading to detrimental cross migration of elements at the boundaries . The core@shell catalysts are proposed as alternative to the mechanical mixture and the hybrid configurations, as the diffusion lengths are significantly reduced ,, while allowing for a better temperature control . Besides, the core@shell design significantly reduces the contact area between the active phases, partially preventing the aforementioned deactivation .…”
Section: Resultsmentioning
confidence: 99%
“… 56 The core@shell configurations instead, consist in the layering of the methanol synthesis and dehydration active phases in a single pellet. 51 , 54 , 55 , 57 66 In the case of MeOH@DME configuration, the CZA catalyst core (brown) is surrounded by a shell of γ-Al 2 O 3 , (gray), whereas in the DME@MeOH, the core and the shell formulations are inverted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simplest system would be mixing the particles or pellets physically on the reactor level (hybrid catalyst bed) [63,133,175]. A physical mixture on the particle level increases the proximity of the active sites for the two reactions and, thus, decreases the probability for the intermediate (MeOH) to leave the reactor without getting dehydrated to DME [176][177][178][179][180][181][182]. For the aforementioned scheme, one could utilize mixing the dried STM-and MTD catalysts [177,180,182].…”
Section: Concepts On Catalyst Application For Direct Dme Synthesismentioning
confidence: 99%